Intervención psicosexual desde el enfoque integrativo. - Rodas Guamán, Sidney Marieta (My University, 2020)
The present work had as objective to propose psychoeducational strategies of sexual orientation from the integrative approach, to a 15 years old adolescent who did not know if to tell the parents about his sexual orientation, the investigation of concepts about sex, gender identity and sexual orientation is primordial to understand scientifically its meaning, on the other hand, the development of the child was necessary to study it by means of Freud's Psychosexual Stages, because since our childhood the main reason is the search of pleasure. Another study within this work was the reactions and thoughts on the part of society and the school context, at the moment that an adolescent manifests his or her sexual orientation, it is not always accepted, the teachers and the social environment are often not prepared, for the reason of ideology, culture and even religion, it is there when they opt for rejection and on several occasions that is the fear for which the adolescent does not manifest himself or herself, it is important to emphasize that there is also a lack of knowledge of this subject, the strategies of psychoeducation are fundamental for this situation.
El presente trabajo tuvo como objetivo proponer estrategias psicoeducativas de orientación sexual desde el enfoque integrativo, a un adolescente de 15 años quien no sabía si decirles a los padres acerca de su orientación sexual, la investigación de conceptos sobre sexo, identidad de género y orientación sexual es primordial para entender científicamente su significado, por otra parte, el desarrollo del niño fue necesario estudiarlo mediante las Etapas Psicosexuales de Freud, por el hecho de que desde nuestra infancia el motivo principal es la búsqueda de placer. Otro estudio dentro de este trabajo fueron las reacciones y pensamientos por parte de la sociedad y el contexto escolar, al momento de que un adolescente manifiesta su orientación sexual, no siempre es aceptado, los docentes y el entono social muchas veces no están preparados, por la razón de ideología, cultura e incluso religión, es ahí cuando optan por el rechazo y en varias ocasiones ese es el temor por la que no se manifiesta el adolescente, es importante recalcar que también existe falta de conocimiento de este tema, las estrategias de psicoeducación son fundamentales para esta situación.
Keywords: ORIENTACION SEXUAL; IDENTIDAD SEXUAL; ENFOQUE INTEGRATIVO; REACCION SOCIAL